Multiple large shareholders and abnormal stock trading halts - Wen Wen; Xiaoqing Feng (China Journal of Accounting Studies (CJAS), 2023)
Using a sample of Chinese A-share listed firms on Shanghai and Shenzhen stock exchanges from year 2003-2019, this paper examines the impact of multiple large shareholders (MLS) on abnormal stock trading halts. The results reveal that listed companies with MLS have a lower probability of abnormal stock trading halts. When the number and share percentage of non-controlling shareholders increase, their inhibitory effect on arbitrary stock trading halts is more significant. Channel tests suggest that MLS can restrain abnormal stock trading halts by reducing the tunnelling activities by controlling shareholders, increasing the proportion of dissenting votes on corporate board, and improving corporate information disclosure quality. The impact of MLS on abnormal stock trading halts is more pronounced in firms with lower quality of internal control and information transparency.
Keywords: 650; corporate governance; information transparency; internal control; Multiple large shareholders; stock trading halts